Two Chancellors: Prince Gortchakof and Prince Bismarck - Klaczko, Julian, 1828-1906; Ward, Frank P. (Salt Lake City, UT : Project Gutenberg, 2012)
"Two Chancellors: Prince Gortchakof and Prince Bismarck" by Julian Klaczko is a historical account written in the late 19th century. The work explores the lives and diplomatic careers of two significant political figures of the time, Prince Gortchakof of Russia and Chancellor Bismarck of Germany. The book aims to analyze their impact on European diplomacy from 1855 to 1871, ultimately suggesting a complex interplay of power between Russia and Prussia that influenced key historical events such as the battles of Sadowa and Sedan. At the start of the text, the translator's preface sets the stage for a deep examination of the diplomatic landscape during a transformative era in Europe. The author, a Polish refugee, presents a vivid portrayal of Gortchakof's early life and education, implying his noble lineage as well as his keen diplomatic skills developed through various posts in the Russian government. The opening also highlights Gortchakof's friendship with Bismarck, suggesting that their collaborative efforts shaped the course of European history. The narrative delves into the challenges both chancellors faced in their political landscapes, underscoring Gortchakof s belief in a strong alliance with Prussia despite underlying tensions and the intricate dynamics that characterized their relationship. (This is an automatically generated summary.)
Release date is 2012-04-28
E-text prepared by Charlene Taylor, JoAnn Greenwood, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Bismarck, Otto, Fürst von, 1815-1898; Gorchakov, Aleksandr Mikhailovich, kniaz', 1798-1883; Europe -- Politics and government -- 1789-1900